Cardiovascular Outcomes in GRADE (Glycemia Reduction Approaches in Type 2 Diabetes: A Comparative Effectiveness Study) - Green, Jennifer B.; Everett, Brendan M.; Ghosh, Alokananda; Younes, Naji; Krause-Steinrauf, Heidi; Barzilay, Joshua; Desouza, Cyrus; Inzucchi, Silvio E.; Pokharel, Yashashwi; Schade, David; Scrymgeour, Alexandra; Tan, Meng H.; et al. (Circulation (New York, N.Y.), 2024)
BACKGROUND: Cardiovascular disease is a major cause of morbidity and mortality in patients with type 2 diabetes. The effects of glucose-lowering medications on cardiovascular outcomes in individuals with type 2 diabetes and low cardiovascular risk are unclear. We investigated cardiovascular outcomes by treatment group in participants randomly assigned to insulin glargine, glimepiride, liraglutide, or sitagliptin, added to baseline metformin, in GRADE (Glycemia Reduction Approaches in Type 2 Diabetes: A Comparative Effectiveness Study). METHODS: A total of 5047 participants with a mean±SD age of 57.2±10.0 years, type 2 diabetes duration of 4.0±2.7 years, and low baseline prevalence of cardiovascular disease (myocardial infarction, 5.1%; cerebrovascular accident, 2.0%) were followed for a median of 5 years. Prespecified outcomes included between-group time-to-first event analyses of MACE-3 (composite of major adverse cardiovascular events: cardiovascular death, myocardial infarction, and stroke), MACE-4 (MACE-3+unstable angina requiring hospitalization or revascularization), MACE-5 (MACE-4+coronary revascularization), MACE-6 (MACE-5+hospitalization for heart failure), and the individual components. MACE outcomes and hospitalization for heart failure in the liraglutide-treated group were compared with the other groups combined using Cox proportional hazards models. MACE-6 was also analyzed as recurrent events using a proportional rate model to compare all treatment groups. RESULTS: We observed no statistically significant differences in the cumulative incidence of first MACE-3, MACE-4, MACE-5, or MACE-6, or their individual components, by randomized treatment group. However, when compared with the other treatment groups combined, the liraglutide-treated group had a significantly lower risk of MACE-5 (adjusted hazard ratio, 0.70 [95% CI, 0.54-0.91]; P=0.021), MACE-6 (adjusted hazard ratio, 0.70 [95% CI, 0.55-0.90]; P=0.021), and hospitalization for heart failure (adjusted hazard ratio, 0.49 [95% CI, 0.28-0.86]; P=0.022). Compared with the liraglutide group, significantly higher rates of recurrent MACE-6 events occurred in the groups treated with glimepiride (rate ratio, 1.61 [95% CI, 1.13-2.29]) or sitagliptin (rate ratio 1.75; [95% CI, 1.24-2.48]). CONCLUSIONS: This comparative effectiveness study of a contemporary cohort of adults with type 2 diabetes, largely without established cardiovascular disease, suggests that liraglutide treatment may reduce the risk of cardiovascular events in patients at relatively low risk compared with other commonly used glucose-lowering medications. REGISTRATION: URL: https://www.clinicaltrials.gov; Unique identifier: NCT01794143.